2022
DOI: 10.1289/ehp11208
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Development in the Presence of Cadmium: An in Vitro Study Using Human Embryonic Stem Cells and Cardiac Organoids

Abstract: Background: Exposure to cadmium (Cd) is associated with cardiovascular diseases. Maternal Cd exposure is a significant risk factor for congenital heart disease. However, mechanisms of Cd on developmental cardiotoxicity are not well defined. Objectives: We evaluated the effects of Cd on the different stages (mesoderm, cardiac induction, cardiac function) of cardiac development using an early embryo development in vitro model and two- or three-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…On the other hand, Zhang et al demonstrated in a basic research study that molecular mechanisms are highly comparable between 2D and 3D (Zhang et al 2015 ). In a work of Wu et al, exposure to cadmium was shown to negatively affect cardiac maturation in both 2D and 3D models, though an effect at lower exposure levels was observed in the first model (Wu et al 2022 ). This was attributed to a lower contact of the 3D organoids to the chemical when compared to the exposed monolayer, which also advocates for a more in vivo like effect of 3D organoids, though sacrificing the sensitivity of the assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Zhang et al demonstrated in a basic research study that molecular mechanisms are highly comparable between 2D and 3D (Zhang et al 2015 ). In a work of Wu et al, exposure to cadmium was shown to negatively affect cardiac maturation in both 2D and 3D models, though an effect at lower exposure levels was observed in the first model (Wu et al 2022 ). This was attributed to a lower contact of the 3D organoids to the chemical when compared to the exposed monolayer, which also advocates for a more in vivo like effect of 3D organoids, though sacrificing the sensitivity of the assay.…”
Section: Discussionmentioning
confidence: 99%
“…Including the PluriLum assay, there are five human stem cell-based reporter cell systems for assessment of toxic effects reported. Three reporter systems are related to expression of NKX2.5 (Fu et al 2019 ; Lauschke et al 2021b ; Wu et al 2022 ), one with TNNT2 (Cao et al 2019 ) and one with MESP1 expression (Pan et al 2018 ), and all of them, with the exception of the one developed by our group (Lauschke et al 2021b ), are based on hESCs.…”
Section: Discussionmentioning
confidence: 99%
“…This innovative approach minimized cardiotoxicity in both hiPSC-CMs and cardiac spheroids while preserving doxorubicin’s anti-cancer effect. In addition to investigating the cardiotoxic effects induced by anti-cancer drugs, cardiac organoids have also recently become a vital tool in exploring the cardiotoxicity arising from environmental pollutants [ 127 ], [ 128 ], [ 129 ]. Following exposure to polystyrene microplastics with a dose equivalent to the exposure level in humans, cardiac organoids exhibited increased oxidative stress, inflammatory response, apoptosis, and collagen accumulation which were consistent with an in vivo study [ 128 ].…”
Section: Applications Of 3d Models In Cardiovascular Researchmentioning
confidence: 99%
“…Similarly, an elegant study revealed that exposure to the transition metal cadmium induced impaired neurogenesis, disruptions in neuronal maturation, and regionalization, as examined in hiPSCs-derived brain organoids incorporated on an array chip with octagon-shaped micropillars . Using a hESC-derived 2D/3D in vitro differentiation model system and cardiac organoids, low-dose cadmium exposure was evidenced to suppress mesoderm formation and consequently inhibit cardiomyocyte differentiation and cardiac induction . Collectively, a handful of studies have demonstrated that human organoid in vitro platforms serve as crucial tools for the safety and toxicity assessment of environmental insults, including emerging environmental pollutants.…”
Section: Organoid-based Models In Environmental Toxicologymentioning
confidence: 99%